Hepatoprotective Effect of Oleuropein-Rich Extract from Olive Leaves against Cadmium-Induced Toxicity in Mice - Hedya Jemai (14571781) (2020)
Cadmium (Cd) is a harmful pollutant which mainly affects the liver and kidney. In this work, we investigated the hepatoprotective effects of olive leaf extract based on oleuropein against hepatic cadmium toxicity in mice. Three groups of animals were used: the first one served as the control (C); the second one received intraperitoneal injection of cadmium 2 mg/kg b.w. (CD), administered five times during two weeks; and the third group received the same doses of Cd and simultaneously 16 mg/kg b.w. of oleuropein. Results showed that Cd induced a significant increase in liver injury biomarkers coupled with enhanced lipid peroxidation (MDA) and significant depletion of antioxidants (CAT and SOD). Histological and immunohistochemical analysis confirmed these findings. In fact, we observed a severe central lobular apoptosis and inflammation around central veins. Cotreatment with oleuropein significantly reduced the oxidative damage induced by cadmium. Our findings suggest that oleuropein could be used in the prevention of Cd hepatotoxicity.  Other information  Published in: BioMed Research International License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1155/2020/4398924